LABOR RESOURCE INTERNATIONALIZATION AS A FACTOR OF THE SUSTAINABLE COMPETITIVENESS - I. Shevchenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper studies a role of labor resource in sustainably oriented international competitiveness. Economic development is now more driven by employment, labor resource and social conditions. That cause a change from economic to sustainably oriented competitiveness, reflecting the increasing role of labor resource and social conditions. Labor resource quality and internationalization n have a long-term influence on the sustainable competitiveness. CEE and NIS countries labor resource and social factors input into sustainable competitiveness are considering. The relevance of economic and social factors of Ukraine international competitiveness is assessed.